2022
DOI: 10.4103/njms.njms_374_21
|View full text |Cite
|
Sign up to set email alerts
|

Mango-shaped Bi-paddled pectoralis major myocutaneous flap reconstruction for large full-thickness defects post resection of squamous cell carcinoma of oral cavity

Abstract: Objectives: The objective of the study was to examine the feasibility of bi-paddled pectoralis major myocutaneous (PMMC) flap reconstruction in patient undergoing full thickness composite resection. Materials and Methods: Inclusion criteria: The subjects chosen were patients with clinically T4A squamous cell carcinoma of buccal mucosa, lower alveolus, and maxilla in with skin involvement. Patients required a full-thickness composite resection of intraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…2,3 Reconstructing composite defects in the head and neck region after oncologic resection involves the reconstruction of multiple layers such as intraoral lining, osseous reconstruction of mandible or maxilla, and soft tissue/skin coverage to achieve adequate sealing of the intraoral defect and visually appealing external skin coverage capable of withstanding adjuvant radiation therapy. [4][5][6] The pectoralis major myocutaneous flap (PMMC) remains the flap of choice for reconstruction of complex full-thickness defects in the head and neck region following ablative resections, despite the availability of microvascular surgery and other free flap reconstructions. 7,8 Noteworthy benefits of PMMC flaps include good vascularity, short learning curve, and reduced requirement for specialized equipment.…”
Section: Official Publication Of Indian Prosthodontic Society Kerala ...mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Reconstructing composite defects in the head and neck region after oncologic resection involves the reconstruction of multiple layers such as intraoral lining, osseous reconstruction of mandible or maxilla, and soft tissue/skin coverage to achieve adequate sealing of the intraoral defect and visually appealing external skin coverage capable of withstanding adjuvant radiation therapy. [4][5][6] The pectoralis major myocutaneous flap (PMMC) remains the flap of choice for reconstruction of complex full-thickness defects in the head and neck region following ablative resections, despite the availability of microvascular surgery and other free flap reconstructions. 7,8 Noteworthy benefits of PMMC flaps include good vascularity, short learning curve, and reduced requirement for specialized equipment.…”
Section: Official Publication Of Indian Prosthodontic Society Kerala ...mentioning
confidence: 99%
“…7,8 Noteworthy benefits of PMMC flaps include good vascularity, short learning curve, and reduced requirement for specialized equipment. 6 Potential complications include orocutaneous fistula (5.2%), partial flap loss (3.5%), flap dehiscence (1.7%), hematoma (1.7%), donor site abscess (1.7%), plate exposure (1.7%). 1,10 Vartanian et al have reported low complication rates with the PMMC flap, for complete and partial flap necrosis of 2.4% and 9.7%, respectively, in 371 cases.…”
Section: Official Publication Of Indian Prosthodontic Society Kerala ...mentioning
confidence: 99%